Harnessing Wisdom: The Role of Indian Knowledge Systems in Promoting Environmental Sustainability - Sharma, Sanjay K. (RSYN Proceedings, 2025)
The Indian Knowledge System (IKS) presents a compelling framework for environmental sustainability, deeply rooted in its rich philosophies, traditions, and ecological practices. Central to IKS is the principle of Ahimsa, or non-violence, which underscores the importance of biodiversity conservation and harmonious coexistence-a theme echoed in foundational texts like the Upanishadsand the Bhagavad Gita. Indigenous water management techniques such as stepwells (baolis), check dams (johads), and tank irrigation have effectively demonstrated sustainable water resource management for centuries. Vedic agricultural practices, including organic farming, crop rotation, and using natural fertilizers like panchagavya, not only enhance soil fertility but also ensure long-term agricultural productivity. Ayurveda advocates for the conservation of medicinal plants, while sacred groves known as Devrai and revered temple forests serve as essential biodiversity reserves. Architectural wisdom from Vastu Shastra informs the design of energy-efficient structures, actively reducing environmental impact and promoting sustainability in our living environments. Additionally, texts such as the Arthashastraand Rigvedaemphasize responsible forest management, encouraging the mindful use of natural resources. Tribal and rural communities contribute significantly through traditional agroforestry and shifting cultivation practices (jhum), diligently working to maintain ecological balance. By integrating ethics with scientific knowledge, the Indian Knowledge System not only addresses contemporary environmental challenges but also provides pathways toward a sustainable and resilient future. Embracing these insights can help foster a world where harmony with nature becomes not just an aspiration, but a lived reality
Keywords: Indian Knowledge System; Environmental Sustainability; Ancient Indian Philosophy; Water Conservation; Medicinal Plants; Agricultural Productivity